(untitled) (Вестник КазНУ. Серия Востоковедения, 2016)
Мақалада ШЫҰ-на мүше мемлекет халықтарының өзара және мемлекетаралық деңгейде шығыс және батыстық мәдениеттердің диалогы талданылады. Given article analyzes dialogue of east and western cultures within the limits of the Shanghai Cooperation Organization, both investigates level of mutual relations of the nations of each state-member of SCO, and relationships of member states of SCO at interstate level for today.